Efficacy Of Vacha–Haridradi Granules In Postpartum Hypogalactia: A Case Study - Koradiya, Heena; Makim, Rita (Journal of Neonatal Surgery, 2025)
Background: Hypogalactia, a common postpartum condition, compromises neonatal nutrition and maternal well-being. The study evaluates the comparative efficacy of Ayurvedic formulation—Vacha–Haridradi Granules on lactation in mothers with Stanya Kshaya. Methods: A 25-year-old primiparous female presented with decreased lactation post-delivery. Clinical signs included soft breasts (Stana Mlaanata), reduced milk (Stanya Alpata), and infant irritability due to hunger. Hematological analysis revealed mild anemia (Hb 10.2 g/dL) with microcytic hypochromic features. Subject given 10g Vacha–Haridradi Granules once daily with cow milk for 30 days. Subjective (Stanya Kshaya symptoms, ejection pattern, suckling frequency, infant well-being) and objective parameters (baby weight gain, breast engorgement score, serum prolactin in a subset) were evaluated. Results: Following the intervention, breastfeeding frequency increased to 9 times/day. Milk ejection improved from drops to a continuous stream. Infant weight increased by 750 grams over 45 days, and serum prolactin levels (measured in a subset) rose from 85 to 112 ng/mL. No side effects were reported during the treatment course. Conclusion: Vacha–Haridradi granules were as effective in managing Stanya Kshaya. The formulation improved lactation metrics with minimal side effects.